Hazard identification, risk assessment and risk control: a study at food manufacturing industry - Othman, Amiruddin; Nazri, Ahmad Nazirul; Birahim, Muhamad Fikri Shahkhirin; Khalid, Amir; Jaat, Norrizam; Sapit, Azwan; Razali, Azahari (Penerbit UTHM, 2020)
Occupational Safety and Health Act (OSHA) is a discipline with broad scope involving many specialized fields. Many researches had been done for determining the relationship between hazard occurring and the control measures which to overcome the hazards. Other than that, occupational health and safety are more likely focus on the social, mental, and physical of surrounding. Nowadays, most of the companies’ workers are lack of safety and health practice which are causes them exposed on dangerous surrounding. In this study, the main objective is to observe the occupational safety and health (OSHA) practise at Koko Minda Food Industries (M) Sdn. Bhd. This study is expected to identify the problem that causes the possible accident and it is prevention in order to reduce the possibility of accident during working. By using Preliminary Hazard Analysis (PHA) and HIRARC form, and interview session of several workers, the data being collected and used as the methodology. From the result and findings, the hazards and control measures are identified so that can able to do some improvement in reducing the accidents and risk while working. Moreover, effective job safety and health training are helping in reducing the risk of accidents while working.